MANAJEMEN PEMERINTAHAN PROGRAM ONE VILLAGE ONE PRODUCT (OVOP) OLEH PEMERINTAH DESA BENAI KECIL KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI TAHUN 2018-2019 - Aini Hafizah; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The enactment of Law Number 6 of 2014 concerning Villages is a great opportunity for the Village to progress, the Village which has been known as an area that is lagging behind in all aspects and a contributor to a fairly high poverty rate. The implementation of the OVOP Program in Indonesia itself still has many problems, including the absence of a clear policy regarding sanctions for regions that do not implement this program and the unclear structure of the responsibility relationship and division of roles. This study used the management theory of the government according to George Terry. The management of the government has four functions, namely planning, organizing, implementing, and supervising. This research was qualitative. With descriptive qualitative method. This research took place in Desa Benai Kecil Kecamatan Benai Kabupaten Kuantan Singingi. The results showed that the Desa Benai Kecil Government in the One Village One Product (OVOP) Program in Desa Benai Kecil did not run well. Judging from the functions of Government Management according to George Terry, namely planning, organizing, implementing, and monitoring that do not work properly. This can be seen from the poor planning that was made, the division of roles and responsibilities that were not clear and firm, the objectives of the OVOP program being implemented in Desa Benai Kecil were not achieved, etc. Keywords: OVOP Planning, OVOP Organizing, OVOP Implementation